Measuring sustainable development macroeconomics and the environment - Atkinson, Giles; Dubourg, Richard; Hamilton, Kirk (Cheltenham Edward Elgar, 1999)
The book contains interesting and readable chapters on the implications of the authors proposed framework for international trade and development planning.It provide the range of measures designed to alert the policy makers to the true trend in the econom
Keywords: Sustainable development; Economic development; Environmental aspects